(untitled) (International Journal of Engineering and Computer Science, 2017)
The robust working and speed of a wireless communication will depend on the speed of the signal we can receive and transmit. Antenna selection can therefore have a significant impact on the working and speed of a wireless link. A microstirp patch antenna has a low profile and weight along with low fabrication cost. In this project, ANSYS HFSS is used to develop and simulate a Microstrip Line Feed Linearly Polarized Rectangular Microstrip Patch Antenna for Wi-Fi at 2.455 GHz.